Hubungan Peran Dosen Pengampu Mata Kuliah dengan Motivasi Belajar Mahasiswa Program Studi Sarjana Keperawatan - Harahap, Rahmat Ali Putra; Laia, Teorida; Sinaga, Elvipson; Batubara, Khairunnisa; Siallagan, Romauli E. G (Universitas Malahayati, 2023)
ABSTRACT Nursing education is an important process that every nurse must go through. For this reason, the first and most important step in the process of nursing professionalism in Indonesia is to organize nursing education as professional education. To educate the nation's life, the role of lecturers is needed to help parents in terms of knowledge, especially cognitive and facilitate the development of individual potential to be able to carry out self-actualization. One of the noble duties carried out by lecturers is not only to teach students but to encourage them to learn more. The purpose of this research is to find out the relationship between the role of the lecturer in charge of the course and the learning motivation of undergraduate nursing students at Audi Indonesia University. This research is a descriptive analytic study with a cross sectional approach. Data collection was carried out using total sampling technique with a sample size of 85 undergraduate nursing students. The study showed that the role of lecturers in nursing was in the very good category of 87.1%. The learning motivation of undergraduate nursing students at Audi Indonesia University is 63.5% of respondents in the high category. There is a significant relationship between the role of lecturers and the learning motivation of undergraduate nursing students at Audi Indonesia University (p value 0.001). Keywords : The Role of Subject Lecturers, Student Learning Motivation ABSTRAK Pendidikan keperawatan merupakan satu proses penting yang harus dilalui oleh setiap perawat. Untuk itu langkah yang paling awal dan penting dilakukan dalam proses profesionalisme keperawatan di Indonesia adalah menata pendidikan keperawatan sebagai pendidikan professional. Untuk mencerdaskan kehidupan bangsa, diperlukannya peran dosen membantu orang tua dalam hal pengetahuan terutama kognitif dan memfasilitasi berkembangnya potensi individu untuk bisa melakukan aktualisasi diri. Salah satu tugas mulia yang diemban dosen tidak hanya untuk mengajar mahasiswa tetapi lebih mendorong mereka untuk belajar. Peneliti ini bertujuan untuk mengetahui hubungan peran dosen pengampu mata kuliah dengan motivasi belajar mahasiswa sarjana keperawatan Universitas Audi Indonesia. Penelitian ini merupakan penelitian sedkriptif analitik dengan pendekatan cross sectional. Pengambilan data dilakukan dengan teknik total sampling dengan jumlah sampel 85 mahasiswa sarjana keperawatan. Penelitian menunjukkan peran dosen sarjana keperawatan berada pada kategori sangat baik sebanyak 87,1%. Motivasi belajar mahasiswa sarjana keperawatan Universitas Audi Indonesia sebanyak 63,5% responden berada pada kategori tinggi. Ada hubungan bermakna antara peran dosen dan motivasi belajar mahasiswa sarjana keperawatan (p value 0,001). Kata Kunci: Peran Dosen Pengampu Mata Pelajaran, Motivasi Belajar Mahasiswa